2021
DOI: 10.3390/ijerph19010228
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Home Advantage during the COVID-19 Pandemic in European Rink Hockey Leagues

Abstract: The primary purpose of the present study was to compare the home advantage (HA) and the home team performance in the most relevant European rink hockey leagues (Spanish, Portuguese and Italian), considering the presence or absence of spectators in the competition venues due to the effect of COVID-19 restrictions. The sample was composed of 1665 rink hockey matches (654 from the Spanish league, 497 from the Portuguese league, and 514 from the Italian league) played between the 2018–2019 and 2020–2021 seasons. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Our review of the research on crowd attendance have shown mixed results, with the majority of studies showing a positive effect of crowd presence on HA (e.g. Arboix-Alió, et al, 2022;Bryson et al, 2021;Correia-Oliveira & Andrade-Souza, 2021;Hill & Van Yperen, 2021;McCarrick, et al, 2021;Scoppa, 2021;Sors et al, 2021), while others found no changes in HA over the seasons analysed (e.g. Almeida & Leite, 2021;Benz & Lopez, 2021;Matos et al, 2021;Wunderlich et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Our review of the research on crowd attendance have shown mixed results, with the majority of studies showing a positive effect of crowd presence on HA (e.g. Arboix-Alió, et al, 2022;Bryson et al, 2021;Correia-Oliveira & Andrade-Souza, 2021;Hill & Van Yperen, 2021;McCarrick, et al, 2021;Scoppa, 2021;Sors et al, 2021), while others found no changes in HA over the seasons analysed (e.g. Almeida & Leite, 2021;Benz & Lopez, 2021;Matos et al, 2021;Wunderlich et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Bryson et al (2021) and Wunderlich et al (2021) examine how soccer matches in front of empty and nearly empty stadiums compares with matches played in stadiums with unrestricted attendance and find evidence of reduced referee bias, but an insignificant effect of empty stadiums on goals scored or match outcomes. Sors et al (2020), in contrast, compare soccer matches played in empty stadiums in 2020 to matches played during the 2016–2019 seasons and finds support for of a weakened home field advantage in games without fans, with similar results identified in Cross & Uhrig (2022) and Scoppa (2021) for European soccer and Arboix-Alió et al (2022) for European rink hockey. Further muddying the mixed evidence in the professional soccer and rink hockey contexts is the fact that these studies rely almost exclusively on comparisons of matches played prior to and subsequent to the widespread COVID-19 pandemic lockdowns, making it impossible to differentiate the impact of empty stadiums from the impact of the pandemic itself.…”
Section: Background and Hypothesesmentioning
confidence: 77%
“…Moreover, even though the top athlete’s performance has been suggested to be boosted by the presence of spectators, the closed-door competitions of the Tokyo Olympics seem to not have hampered swimmers’ performances, maybe due to the athletes’ positive attitude and probable eagerness to compete, that could have counteracted the absence of spectators. Indeed, in team sports home advantage does not disappear without home crowds, suggesting that there could probably be multiple and complementary reasons that would also explain the better performance on the home court and playing without spectators, such as court dimensions, playing surface or travel fatigue [ 41 , 42 , 48 ].…”
Section: Discussionmentioning
confidence: 99%